Faktor-Faktor Yang Beresiko Terjadinya Pasien Stagnan Di Instalasi Gawat Darurat Rumah Sakit - Puti Damayanti; Sutono Sutono (PSIK FKKMK UGM, 2017)
Background: Fast response is needed in the Emergency Room (ER). However, the high number of patient visit leads stagnant patient in ER. The impact of patient stagnant can affect other patient safety and quality of services in the hospital.Objective: Identify factors related to the presence of stagnant patients in the ER of Dr. Sardjito General Hospital.Methods: This study used a retrospective case control method. The total samples in this study is 87 samples and divided into two groups, 29 samples for non-stagnant group and 58 samples for stagnant group. Data collection used non-probability sample with purposive sampling method for the sample selection. Sampling was carried out at 16 to 28 January 2015 in ER of Dr. Sardjito General Hospital. This research uses Chi Square and logistic regression to data analyze.Results: Risk factors to stagnant patients are the availability of beds (p: <0.001), corresponding ward grouping disease patients (p: 0.021), fogging (p: 0.008), age of the patient (p: <0.001), patients came hours ( p: 0.019) and the number of actions in Emergency Room (p: 0.002). From the results of logistic regression the most influential factor for the patients is the availability of beds (15 times more risky).Conclusions: Factors related to patients are the availability of a stagnant, according grouping wards patient's disease, fogging, patient age, patient coming hours and the number of actions.ABSTRAKLatar belakang: Pelayanan yang cepat sangat dibutuhkan di IGD. Akan tetapi kondisi kunjungan pasien di IGD yang cukup banyak dapat menimbulkan pasien stagnan di IGD . Dampak pasien yang stagnan mempengaruhi keselamatan pasien yang lain dan mutu pelayanan rumah sakit tersebut.Tujuan: Mengetahui faktor-faktor yang berisiko terjadinya pasien yang stagnan di Instalasi Gawat Darurat Rumah Sakit Umum Pusat Dr. Sardjito Yogyakarta.Metode: penelitian ini menggunakan metode case control retrospektif dengan jumlah sampel masing-masing 29 sampel untuk kelompok non-stagnan dan 58 sampel untuk kelompok stagnan. Pengambilan data dilakukan dengan cara non-probability sample dengan metode purposive sampling. Pengambilan sampel dilakukan pada 16-28 Januari 2015 di IGD RSUP Dr. Sardjito Yogyakarta. Analisa yang digunakan di dalam penelitian ini antara lain Chi Square dan regresi logistik.Hasil: Faktor-faktor yang berisiko pasien stagnan antara lain ketersediaan tempat (p:<0,001), bangsal sesuai pengelompokkan penyakit pasien (p:0,021), fogging(p:0,008), usia pasien(p:<0,001), jam datang pasien(p:0,019) dan jumlah tindakan(p:0,002). Dari hasil regresi logistik faktor yang paling berisiko dengan terjadinya pasien stagnan adalah ketersediaan tempat (15 kali lebih berisiko)Kesimpulan : Faktor-faktor yang berhubungan dengan pasien stagnan antara lain ketersediaan tempat, bangsal sesuai pengelompokkan penyakit pasien, fogging, usia pasien, jam datang pasien dan jumlah tindakan.